Binding Energy of the One-Sided Dielectrically Enhanced Screened Exciton in Semiconductor Quantum Well - K. H. Aharonyan; N. B. Margaryan (ՀՀ ԳԱԱ հրատ.)
A formalism for the study of the two-dimensional screened exciton states in onesided strong dielectric contrast affected ternary quantum well (QW) system modeled by the two-dimensional Debye-Hückel-type potential is presented. В модели двумерного дебай-хюккелевского потенциала взаимодействия в трехслойной квантовой яме представлен формализм для исследования экранированных экситонных состояний с учетом одностороннего сильного контраста диэлектрических постоянных. Երկչափ դեբայ-հյուկելյան բնույթի փոխազդեցության պոտենցիալի կիրառությամբ ներկայացված է եռաշերտ քվանտային փոսում երկչափ էկրանավորված էքսիտոնային վիճակների ուսումնասիրությունը՝ դիէլէկտրական հաստատունի մեկկողմանի կտրուկ թռիչքի հաշվառումով:
Keywords: Physics; Science